Status, population fluctuations and ecological relationships of Peary caribou on the Queen Elizabeth Islands: Implications for their survival - Miller, Frank L.; Gunn, Anne (Rangifer, 2003)
The Peary caribou (Rangifer tarandus pearyi) was recognized as 'Threatened' by the Committee on the Status of Endangered Wildlife in Canada in 1979 and 'Endangered' in 1991. It is the only member of the deer family (Cervidae) found on the Queen Elizabeth Islands (QEI) of the Canadian High Arctic. The Peary caribou is a significant part of the region's biodiversity and a socially important and economically valuable part of Arctic Canada's natural heritage. Recent microsatellite DNA findings indicate that Peary caribou on the QEI are distinct from caribou on the other Arctic Islands beyond the QEI, including Banks Island. This fact must be kept in mind if any translocation of caribou to the QEI is proposed. The subspecies is too gross a level at which to recognize the considerable diversity that exists between Peary caribou on the QEI and divergent caribou on other Canadian Arctic Islands. The Committee on the Status of Endangered Wildlife in Canada should take this considerable diversity among these caribou at below the subspecies classification to mind when assigning conservation divisions (units) to caribou on the Canadian Arctic Islands. In summer 1961, the first and only nearly range-wide aerial survey of Peary caribou yielded a population estimate on the QEI of 25 845, including about 20% calves. There was a strong preference for range on the western QEI (WEQI), where 94% (24 363) of the estimated caribou occurred on only 24% (ca. 97 000 km2) of the collective island-landmass. By summer 1973, the overall number of Peary caribou on the QEI had decreased markedly and was estimated at about 7000 animals. The following winter and spring (1973-74), the Peary caribou population declined 49% on the WQEI. The estimated number dropping to
Keywords: populations fluctuations; Queen Elisabeth Islands; arctic Canada; die-offs; ecology; genetics; population estimates; Rangifer tarandus pearyi; taxonomy